Implementation of Multicultural Values in Science Learning in Primary Schools - Prananda, Gingga; Tubo, Mariane Bitacura; Judijanto, Loso (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the implementation of multicultural values in primary school science instruction. The research employed a descriptive qualitative approach using a case study design. The study was conducted at SDN 13 Lolong Belanti, Padang City, West Sumatra, with research participants comprising one principal, two fifth-grade teachers, and two fifth-grade classes totaling 30 students. Data were collected through observation, interviews, and documentation. Data analysis was carried out using an interactive analysis model, which included data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that multicultural values such as tolerance, cooperation, mutual respect, fairness, and openness to differences have been implemented in science learning through social interactions and classroom management practices. However, the implementation of these values remains implicit and has not yet been systematically integrated into science lesson planning.